Ecological modernisation, environmental policy and innovation: priorities for the Asia-Pacific region. (24th February 2004) - Welford, Richard; Hills, Peter
This paper explores various dimensions of ecological modernisation in the context of developments in environmental policy and technological innovation in the Asia-Pacific region. It argues that models of ecological modernisation emerging in the region will differ from those developed elsewhere, particularly in Europe. Nonetheless, ecological modernisation theory can help to inform decisions surrounding the application of technological innovation which can then be applied to tackle environmental issues and at the same enhance the business competitiveness of firms in Asia and the Pacific.